Private international law aspects of corporate social responsibility - Kessedjian, Catherine; Cantú Rivera, Humberto (Ius comparatum - global studies in comparative law, 2020)
Part I -- General Report -- Questions de droit international privé de la responsabilité sociétale des entreprises : Rapport général -- Part II National Reports -- Argentina -- Belgium -- Brazil -- Canada -- Chile -- China -- Colombia -- Czech Republic -- France -- Germany -- Italy -- Japan -- Kazakhstan -- Mexico -- The Netherlands -- Portugal -- Switzerland -- Turkey -- United Kingdom -- Vietnam.